The evaluation on anticancer properties from kenaf seeds oil from different varieties - Amid, Azura; Jamal, Parveen; Mohamad, Nurul Elyani; Engku Abdullah, Engku Hasmah (IIUM Press, 2011)
Kenaf (Hibiscus cannabinus) from the family of Malvaceae is a valuable fibre plant native to India and Africa. Kenaf is composed of various active components including tannins, polyphenolics, alkaloids, essential oils and steroids. In this study, kenaf seeds oil was used as a material in observing the anticancer activity on MCF-7 cancer cells line and finding the optimum parameter to extract the oil that give the highest anticancer activity. Three varieties of kenaf seeds were utilized and their seeds were screened for their anticancer properties. Khon kaen shows the highest anticancer activity with the ICso value of 229.17 ~g/mL.